Um olhar sobre a evolução dos suportes informacionais: mineral e vegetal - PAIVA, Vívian Daniele Ferreira (2017)
It presents the evolution of informational support referring to the mineral support (clay tablets) and plant (papyrus and paper) and how their historical records, cultural and religious endured over time. Briefly describes how was the transition from one support to another, and the reasons that led to changes over time, until the digital age in which modern information technology, living with paper. Used as a qualitative research methodology of bibliographic nature with emphasis on collections of scholarly articles, books in the field biblioteconômico and websites with information relevant to the composition of the content. It concludes that the informational support play a critical and essential role in recording and transmission of historical-cultural-religious knowledge from the ancient societies evolve over time to meet new demands and requirements of use of the information of the new emerging companies.